The New Theology and the Social Movement - Campbell, J.
ill. Verbatim Report of Addresses delivered at a Meeting of the Independent Labour Party, in Hope Hall, Liverpool, on March 25th, 1907. - Reprinted from "The Christian Commonwealth".